Localized cystic disease of the kidney: A rare diagnosis of this uncommon condition in a child - Christopher A. Behr; Anthony J. Hesketh; Alex K. Williamson; Samuel Z. Soffer; Richard D. Glick (Elsevier, 2016)
Localized cystic disease of the kidney (LCDK) is a rare condition found primarily in adults, with the total number of documented cases less than 75. Its incidence in the pediatric population is even more minuscule. It is a benign condition, but can be difficult to classify with certainty on imaging, often necessitating surgical excision to adequately rule out a malignancy. We present the case of a six-year-old child with a cystic mass of the kidney who underwent a radical nephroureterectomy, for which pathology showed LCDK. We then review the literature on the subject.